Fekete–Szegö Problems for Certain Classes of Meromorphic Functions Involving q-Al-Oboudi Differential Operator - M.K. Aouf; Fatma Z. El-Emam (Journal of Mathematics)
In this paper, we introduce a new derivative operator involving q-Al-Oboudi differential operator for meromorphic functions. By using this new operator, we define a new subclass of meromorphic functions and obtain the Fekete–Szegő inequalities.